(NwYRAVENIE PROSTRANSTWENNYH OTNO[ENIJ W QZYKAH dAGESTANA (B:s ((NtEMATI^ESKIJ SBORNIK(B) /s - (NaTAEW(B, (Nb(B.(Nm(B.s ((NmAHA^KALA (B:s (Nan sssr(B. (Ndf(B,s, 1990)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NdAGENSTANSKIJ FILIAL an sssr(B. (NiN(B-(NT ISTORII(B, (NQZYKA I LITERATURY IM(B. (Ng(B. (NcADASYs
Keywords: (NgRAMMATIKAs; (NdAGESTANSKIE QZYKIs